Improving the Ability to Read the Qur'an through the Talaqqi Method in the Congregation of the Ta'lim Assembly in Tembilahan Barat Village, Indragiri Hilir - Nur Komariah (Jurnal Masyarakat Mengabdi, 2026)
The ability to read the Qur'an in accordance with the rules of tajwid and makharijul letters is a fundamental skill for every Muslim. However, initial observations at the Majelis Ta'lim of Tembilahan Barat Village, Indragiri Hilir Regency, Riau Province, showed that most of the congregation (75%) still had difficulties in pronouncing letters according to their makhraj and applying the rules of recitation correctly. This community service activity aims to improve the congregation's Qur'anic reading ability through the implementation of the talaqqi method based on direct practice and individual correction. The implementation method consisted of three stages: initial assessment (pre-test), intensive mentoring for 12 weeks using the talaqqi and musyafahah methods, and final evaluation (post-test). The participants were 30 women members of the Majelis Ta'lim congregation. The results showed a significant improvement in the participants' Qur'anic reading ability. The average pre-test score of 58.4 (poor category) increased to 84.6 (good category) in the post-test, with an N-Gain value of 0.73 (high category). As many as 83% of participants achieved the minimum mastery score in the aspect of makharijul letters, while 77% of participants showed improvement in the application of tajwid rules. This activity concludes that the talaqqi method is effective in improving the ability to read the Qur'an in adult congregations at the Majelis Ta'lim. Recommendations of this activity are the formation of independent learning groups (halaqah) and peer tutor training for program sustainability.